The Role of Socioeconomic Status and Social Determinants in Predicting Accessibility and Barriers to Mental Health Services in the Canadian General Population - Elliott, Katherine, Pauline (Université d'Ottawa / University of Ottawa, 2015)
There is a tremendous discrepancy between the number of people likely meeting criteria for a mental disorder or substance dependence in Canada and the number of people actually receiving mental health or substance dependence treatment. Thus, it is important to examine what facilitates entrance into the mental health care system and what prevents people from receiving the treatment they need. Mixed findings exist as to whether socioeconomic status (SES) and other social determinants of health play a role in receiving treatment in Canada. However, due to several methodological issues with previous studies that have examined this issue, three studies were designed to re-examine and add to the literature in this area by investigating: (1) whether SES (i.e., income and education) and other social determinants as well as psychological distress predict the number of services received by any professional for any mental disorder or substance dependence, as well as predict overall satisfaction with the services received (2) the psychometric validity and reliability of the 3-factor model proposed by Statistics Canada to measure barriers due to accessibility, acceptability and availability, and (3) whether SES, other social determinants and psychological distress predict specific barriers to receiving mental health treatment for an unmet need. All data were obtained from the Canadian Community Health Survey, cycle 1.2, Mental Health and Wellbeing. In Study 1, the SES/social determinants model predicted the number of services received for both medication and psychotherapy. Out-of-pocket spending, was the strongest predictor of the number of consultations from any provider, however it was also inversely related to overall satisfaction with services. Higher levels of distress predicted greater dissatisfaction with services received. Study 2 revealed that the three factor model of accessibility, acceptability and availability was invalid and unreliable as a measure of barriers to mental health services. It is, therefore, recommended that each specific barrier be treated as an independent causal indicator of an index measuring overall accessibility to mental health services. Finally, in Study 3, when examining each barrier independently, both education and income played important roles in recognizing there was a problem, seeking services, and actually accessing the services needed. Other social determinants also played important roles which differed depending on the type of barrier being examined. The results of the three dissertation studies indicate a clear relation between SES, other social determinants and psychological distress, and accessibility and barriers to mental health services in Canada for those suffering any mental disorder or issue related to substance dependence. The findings have significant implications in terms of potential policy implications, recommendations for the design of future national level surveys, and recommendations for future research on this topic.
Keywords: Socioeconomic Status; Accessibility; Barriers; Mental Health Services